Estratégia leitora como um caminho para a melhora da compreensão do gênero notícia dos alunos dos 3° anos - Nunes, Edison Deny Telles (2020)
This research is located in the area of Portuguese Language, line of research Text and Discourse in Oral and Written Modalities and presents a reading strategy to improve the understanding of the news genre of students from the 3rd years of high school in a private school in the state of Sao Paulo. Thus, based on studies of textual linguistics by (Van Dijk 1990), which also aims at the text as a basic unit of study, reading strategies by (Isabel Solé 1998) and (Angela Kleiman 1989 and 1997), which present some strategies reading as a cognitive process of great importance for understanding texts and the world, we seek to build a temporal plot about the act of reading and its consequences. The problem therefore consists in the low performance of 3rd year students in the process of understanding texts of the news genre before and after the application of studies of the superstructure of the textual genre (Van Dijk 1990) and, thus, to diagnose whether there was or not some progress in that process. The general objective of this work is to contribute with new studies on the performance of high school students in relation to the interpretation of texts, that is, the process of acquisition of reading competence, specifically of the news text genre. The specific objectives are characterized by: I) Reviewing historical aspects of changes in the process of reading practice together with social aspects; II) Characterize the reading difficulties of students from the 3rd years of high school; III) Analyze the students 'responses after reading a news item for which the textual composition had already been given, confronting and discussing the results obtained from the students' reading. In addition, we present a historical overview of the development process of the act of reading, some numbers of the students' performance in acquiring reading competence and analysis of texts of the news genre requested to students of the 3rd years of high school. In view of the above, we conclude that, after all these reflections, there is a need for further studies in relation to the pedagogical practice of teachers in the classroom, so that, thus, search for new indexes, which are satisfactory, in order to provide better conditions for the acquisition of reading competence for 3rd year students